Performance Analysis of Thermoelectric Cooler Box with Water Cooling Block (WCB) and Heat Sink Fan - I Wayan Sutina; Adi Winarta; I Nyoman Agus Adi Saputra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Thermoelectric cooler boxes offer an environmentally friendly, energy-efficient, and portable cooling solution. However, the performance of thermoelectric cooling systems is highly dependent on the effectiveness of heat dissipation on the hot side of the Peltier module (TEC). This study aims to experimentally investigate the impact of using a Water Cooling Block (WCB) compared to a conventional heat sink fan on the cooling performance of a thermoelectric-based cooler box. The experimental setup involved two configurations for the hot side cooling system, where parameters such as hot-side temperature, cabin temperature, and Coefficient of Performance (COP) were measured and analyzed. The experimental results showed that the use of WCB was able to significantly reduce the temperature on the hot side, with a temperature reduction in the cabin reaching 20.35 °C and an average COP of 0.09687. Meanwhile, the TEC-fan temperature in the cabin cooler box was lower at 21.45 °C, with an average COP value of 0.04718. Therefore, the Water Cooling Block demonstrates superior efficiency and thermal management compared to the heat sink fan, offering enhanced performance for thermoelectric cooler box applications in various low-temperature storage needs.